Acute Urinary Retention in an Old Male Caused By a Prostatic Urethral Polyp (Annals of Medical Research, 2021)
None
Keywords: Acute urinary retention, Prostatic urethral polyp, Posterior urethral valve, Transurethral resection, Cystoscopy.